Microemulsion Polydispersion Due to Polymer Solubilization - Radiman, Shahidan (Universiti Putra Malaysia Press, 1996)
Freeze-fracture electron microscopy results on water-in-oil microemulsion showed that significant polydispersion can be induced by adding water soluble polymers.